2016
DOI: 10.1109/tnsre.2015.2475724
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Mediated Imitation Skill Training for Children With Autism

Abstract: Autism spectrum disorder (ASD) impacts 1 in 68 children in the US, with tremendous individual and societal costs. Technology-aided intervention, more specifically robotic intervention, has gained momentum in recent years due to the inherent affinity of many children with ASD towards technology. In this paper we present a novel robot-mediated intervention system for imitation skill learning, which is considered a core deficit area for children with ASD. The Robot-mediated Imitation Skill Training Architecture (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 33 publications
2
62
0
Order By: Relevance
“…The participants in this study showed clear interest in the robots and responded positively and correctly to them throughout the treatment sessions. These results were generally in line with those of previous studies using robots as cotherapists in the treatment of ASD [Zheng et al, ]. As in previous studies with humanoid robots, the participants in this study showed behaviors that children normally exhibit toward other humans during play, such as singing with them, asking questions, proposing play activities, or talking to them [Chaminade et al, ; Pierno, Mari, Lusher, & Castiello, ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The participants in this study showed clear interest in the robots and responded positively and correctly to them throughout the treatment sessions. These results were generally in line with those of previous studies using robots as cotherapists in the treatment of ASD [Zheng et al, ]. As in previous studies with humanoid robots, the participants in this study showed behaviors that children normally exhibit toward other humans during play, such as singing with them, asking questions, proposing play activities, or talking to them [Chaminade et al, ; Pierno, Mari, Lusher, & Castiello, ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings were similar to those of previous robot studies, in which performances in various areas, such as eye contact, motor imitation, and speech expression, were generally better with robot‐mediated treatment than with human therapist‐mediated treatment[Bird, Leighton, Press, & Heyes, ; Kim et al, ]. The better performances, especially in the initial sessions, in the robot‐treatment groups might be attributable to higher attentional preferences for the robotic prompts than those of humans [Zheng et al, ]. The improvements in the frequency of eye contact attenuated after the fourth session in the TG but continued to gradually increase in the CG.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Prior to our study, we did not consider including virtual characters and robots as actors in the analysis, but in some cases, they took the human therapist's role as they gave instructions or prompts to the autistic user with therapeutic purposes [6,59]. Besides, human-robot interaction studies in autism have been proving that robots' presence and guidance can be more efficient than humans' in educational and therapeutic settings [59]. Thus, their involvement in future studies may not only be based on how the users interact with them, but also how robots take roles in UX studies as actors.…”
Section: Discussionmentioning
confidence: 99%
“…the immersive room in [16]) or objects (e.g. the watch in [58] or the chair in [59]) used. These behaviors may result in irreversible situations leading to session cancellations.…”
Section: Environment Tools and Materialsmentioning
confidence: 99%